2017
DOI: 10.1002/jcb.25844
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Cytotoxic Activity in Leukemic Lineages Reveals Important Features of β‐Hairpin Antimicrobial Peptides

Abstract: Several reports described different modes of cell death triggered by antimicrobial peptides (AMPs) due to direct effects on membrane disruption, and more recently by apoptosis and necrosis-like patterns. Cytotoxic curves of four β-hairpin AMPs (gomesin, protegrin, tachyplesin, and polyphemusin) were obtained from several human leukemic lineages and normal monocytes and Two cell lines were then selected based on their cytotoxic sensitivity. One was sensitive to AMPs (K562) and the other resistant (KG-1) and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(31 citation statements)
references
References 36 publications
4
27
0
Order By: Relevance
“…Comparison of our results with those reported previously indicated that synthetic and modified at N‐ and C‐terminus AMPs demostrate a higher cytotoxic propensity. In particular, the IC 50 values determined by Rodrigues et al for the synthetic gomesin bearing the N‐terminal pyroglutamic acid and the amidated C‐terminus averaged out at 2.87 and 8.13 μ m against HeLa and SKBR‐3 cell lines, respectively.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Comparison of our results with those reported previously indicated that synthetic and modified at N‐ and C‐terminus AMPs demostrate a higher cytotoxic propensity. In particular, the IC 50 values determined by Rodrigues et al for the synthetic gomesin bearing the N‐terminal pyroglutamic acid and the amidated C‐terminus averaged out at 2.87 and 8.13 μ m against HeLa and SKBR‐3 cell lines, respectively.…”
Section: Discussionsupporting
confidence: 82%
“…IC 50 values for lactoferricin B in case of human neuroblastoma cell lines ranged from 15 to 60 μ m ; α‐defensins 1–3 at a concentration of 15 μ m decreased the metabolic activity of lung cancer cells by 2.5 times . Synthetic protegrin caused death of 50% of erythroleukemia cells at concentrations of 12 μ m . It is noteworthy that the synthetic protegrin was amidated at the C‐terminus of the polypeptide chain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The in-vitro anti-cancer activity of Gm has been demonstrated in a number of studies using a range of murine and human cancer cell lines [ 3 , 9 , 12 , 13 , 14 , 15 , 16 ], as well as cells from devil facial tumour disease (DFTD) [ 18 ]. Table 2 summarises the anti-cancer activity of Gm on the most commonly tested cell lines.…”
Section: Cytotoxic and Haemolytic Activity Of Gomesinmentioning
confidence: 99%
“…Like many other AMPs, Gm shows cytotoxic activity against a wide range of pathogens, including clinically-relevant Gram-positive and Gram-negative bacteria, fungi and yeast, as well as demonstrating anti-malarial [ 3 , 4 ], anti-cryptococcal [ 5 ], and anti- Leishmania activity [ 1 , 3 , 6 , 7 , 8 , 9 , 10 , 11 ]. Gm also has in-vivo anti-cancer activity in a mouse model of melanoma [ 12 ], and in-vitro activity against a number of other human cancers [ 3 , 9 , 12 , 13 , 14 , 15 , 16 , 17 ]. In addition, Gm shows cytotoxic and anti-proliferative activity against devil facial tumour disease [ 18 ], a “parasitic” form of cancer that threatens the extinction of the Tasmanian devil ( Sarcophilus harrisii ), a unique Australian animal.…”
Section: Introductionmentioning
confidence: 99%